PENGARUH PDRB TERHADAP TINGKAT KEMISKINAN DI PROVINSI SULAWESI TENGAH (TAHUN 2013-2015) - Nugroho, Moh Agus; Rhamadhani, Rika Febby (Institut Agama Islam Bengkulu, 2016)
This study examines the Influence of GDP on Level of Provery in Central Sulawesi in 2013 – 2015. The purpose of this research is to analyze how influence GDP on Level of Proverty in Central Sulawesi. The method of analysis used qualitative and quantitative. The type of quantitative research is used to describe of phenomena related to problems on this study. While type of qualiative research is used to analyze the information that can be measured. The result of this study indicate that GDP is not significant effect on Level of Proverty. This is due to the increase GDP that occurred in central sulawesi is not always followed by decrease on the level of proverty. It can be seen from data of GDP and level of provery in Central Sulawesi in 2013 – 2015.Key words : Level of Provery, GDP